2009
DOI: 10.1029/2008jf001099
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of braided channel pattern response to increased discharge

Abstract: [1] Physical models of gravel braided rivers were used to investigate the adjustment of braiding intensity to step changes in channel-forming discharge and the mechanisms by which channel pattern adjustment and maintenance occurs. A braided channel developed at low discharge was subjected to two step increases in discharge between which the channel was given time to develop stable average braiding intensity in response to each steady discharge. Active (with visible bed material movement) and total channel netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 58 publications
15
109
0
Order By: Relevance
“…However, other studies have shown that discharge variation has a large effect on river morphology (e.g., Kiss and Sipos, 2007;Crosato and Saleh, 2010) due, among other things, to vegetation colonization on exposed bar sections (Gordon and Meentemeyer, 2006;Tealdi et al, 2011). Also, Egozi and Ashmore (2009) demonstrated that braiding intensity increased with increasing discharge, although this was temporary and braiding intensity decreased after the channel adapted to the new discharge. In the context of both river training and morphological studies, the effects of discharge variation on the braided river network are still largely unknown.…”
Section: Disturbances In Braiding Riversmentioning
confidence: 70%
“…However, other studies have shown that discharge variation has a large effect on river morphology (e.g., Kiss and Sipos, 2007;Crosato and Saleh, 2010) due, among other things, to vegetation colonization on exposed bar sections (Gordon and Meentemeyer, 2006;Tealdi et al, 2011). Also, Egozi and Ashmore (2009) demonstrated that braiding intensity increased with increasing discharge, although this was temporary and braiding intensity decreased after the channel adapted to the new discharge. In the context of both river training and morphological studies, the effects of discharge variation on the braided river network are still largely unknown.…”
Section: Disturbances In Braiding Riversmentioning
confidence: 70%
“…During the period of analysis, a large proportion of the bed area was reworked by processes typical of braided rivers, i.e., channel avulsions, bar migration, bedload transport, confluence and bifurcation evolution, and active and non-active anabranches (e.g., Egozi and Ashmore, 2009). Natural grain sorting is observed over the entire bed surface; fine and coarse sediments are organized in relation to local topography, flow bifurcation, bed roughness or flow constriction, which lead to a complex pattern of different surface grain size (e.g., Carson and Griffiths, 1987).…”
Section: Natural and Modeled Surface Grain Sortingmentioning
confidence: 99%
“…It can be observed that the development of a braided pattern in the predicted river shares many common properties with the experimental river ( Figure 5, activity number identified with Figure 4). Most of the morphologic elements and activities observed in the experimental river [31] have been found in the predicted river.…”
Section: River Evolution Processes and Phenomenamentioning
confidence: 97%
“…The model was applied to a laboratory experiment conducted by Egozi and Ashmore [31], in which a braided river pattern was generally developed. The river was originally designed to be a generic Froude-scaled model with the prototype being the Sunwapta River in Canada.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation